Managing wound complications in hypoglossal nerve stimulation: Prevention strategies and criteria for avoiding device explantation - Kai-Yuan Hsiao; Martha Lucía Gutiérrez Pérez; Patrícia S. Cé; Thomaz Fleury Curado (Oral and Maxillofacial Surgery Cases)
Hypoglossal nerve stimulation is a proven treatment for obstructive sleep apnea, yet its invasive nature raises concerns about wound complications. This case series examines three distinct postoperative scenarios: (1) early infection in a patient with poor glycemic control and inadequate self-care, (2) late-stage infection in a patient with prolonged device non-use, and (3) early wound dehiscence caused by nonadherence to postoperative restrictions, successfully managed with a novel wound management protocol that preserved the device. These cases highlight the importance of comprehensive risk assessment, adherence to postoperative guidelines, the control of metabolic diseases and individualized management strategies to preserve device functionality while reducing healthcare costs. Notably, this is the first report demonstrating successful device retention in hypoglossal nerve stimulation despite wound dehiscence. Further studies are essential to refine risk stratification and establish evidence-based treatment protocols for this innovative and increasingly utilized therapy.